PAI DI TENGAH KRISIS KEMANUSIAAN: SOLIDARITAS GLOBAL BERBASIS PENDEKATAN HUMANIORA - Ilal Maisarah (Yayasan An-Nur Meunara Baro, 2025)
Global humanitarian crises including armed conflict, refugee displacement, and climate change demand educational responses grounded in universal human values. This article analyzes the potential of Islamic Religious Education (PAI) to foster global solidarity through the lens of the humanities, encompassing philosophy, literature, arts, and history. Using a qualitative case study method, the research explores PAI programs implemented in crisis-affected regions (such as Turkey, Lebanon, and Indonesia) and conducts textual analysis of Islamic teachings on social compassion. The findings indicate that: (1) Islamic values of ukhuwah basyariyah (universal human brotherhood) can be recontextualized through narrative and artistic methods, such as employing the Prophet’s Hijrah as an analogy for modern-day displacement; (2) Aesthetic and reflective learning approaches, such as refugee poetry and collaborative murals, effectively cultivate empathy among students; and (3) Interfaith humanitarian projects rooted in the humanities such as peace theater and art workshops help reduce stereotypes and religious prejudice. This study proposes a transformative PAI framework that is responsive to global humanitarian challenges and underscores the relevance of integrating Islamic spirituality with the universal language of the humanities.